High Fidelity Simulation Experience in Emergency settings: doctors and nurses satisfaction levels - Calamassi, Diletta; Nannelli, Tiziana; Guazzini, Andrea; Rasero, Laura; Bambi, Stefano (Acta Biomedica Atenei Parmensis, 2016)
Background and aim of the work: Lots of studies describe High Fidelity Simulation (HFS) as an experience well-accepted by the learners. This study has explored doctors and nurses satisfaction levels during HFS sessions, searching the associations with the setting of simulation events (simulation center or on the field simulation). Moreover, we studied the correlation between HFS experience satisfaction levels and the socio-demographic features of the participants. Methods: Mixed method study, using the Satisfaction of High-Fidelity Simulation Experience (SESAF) questionnaire through an online survey. SESAF was administered to doctors and nurses who previously took part to HFS sessions in a simulation center or in the field. Quantitative data were analyzed through descriptive and inferential statistics methods; qualitative data was performed through the Giorgi method. Results: 143 doctors and 94 nurses filled the questionnaire. The satisfaction level was high: on a 10 points scale, the mean score was 8.17 (SD±1.924). There was no significant difference between doctors and nurses satisfaction levels in almost all the SESAF factors. We didn’t find any correlation between gender and HFS experience satisfaction levels. The knowledge of theoretical aspects of the simulated case before the HFS experience is related to a higher general satisfaction (r=0.166 p=0.05), a higher effectiveness of debriefing (r=0,143 p=0,05), and a higher professional impact (r=0.143 p=0.05). The respondents that performed a HFS on the field, were more satisfied than the others, and experienced a higher “professional impact”, “clinical reasoning and self efficacy”, and “team dynamics” (p< 0,01). Narrative data suggest that HFS facilitators should improve their behaviors during the debriefing. Conclusions: Healthcare managers should extend the HFS to all kind of healthcare workers in real clinical settings. There is the need to improve and implement the communication competences of HFS facilitators.